Factors associated with functional status among free-living elderly in Mukim Batu, Gombak, Malaysia - Murat, Muhammad Faizal (2015)
Globally, the population of older people is on the rise and has the fastest growing rate in the light of the universal decline in fertility and the increase in life expectancy. The rapid ageing population will indirectly leads to an increasing number of disabled older people that will adversely affect their ability to carry out daily tasks independently. Thus, functional decline among the aged should become a growing concern. The main objective of this study is to determine the prevalence and factors that predict functional status among the free-living elderly. A cross-sectional study was conducted in Mukim Batu, sub-district of Gombak, Selangor. Two hundred and fifty eight older people aged within 60 to 88 years were undergone tests of functional status (self-reported physical disability and performance-based functional limitation). Instrumental Activities of Daily Living (IADL) instrument were used to assess self-reported physical disability, whereas performance-based functional limitation were assessed in terms of cognitive functioning, mobility status, manual dexterity and muscle strength performance. Factors associated (socio-demographic, lifestyle, presence of chronic diseases, psychosocial, risk of falls and anthropometric indicators) with self-reported physical disability were tested. The same approach to examine the associations between these factors and each functional limitation were carried out. Physical disability as assessed using IADL reveals that more than half (58.1%) of the respondents were fully dependent (IADL<8). In terms of functional limitation, the prevalence of cognitive impairment [Elderly Cognitive Assessment Questionnaire (ECAQ)<6] and mobility dependent [Elderly Mobility Scale (EMS)<14] were low, at almost four percent each. Manual dexterity as using a lock and key test to assess the ability of the respondents to make coordinated hand and finger movements showed that only 4.7% of them were unable to perform the task. In Binary logistic regression (LR) analyses, factors found to be remained significantly predict IADL physical disability were advanced age (≥75 years: OR 6.4; 95% CI 1.3, 30.8), unmarried (OR 2.5; 95% CI 1.1, 5.9), unemployed/retired (OR 2.3; 95% CI 1.2, 4.3), and at risk of falls (OR 2.5; 95% CI 1.3, 6.1) with Nagelkerke R Square shows that about 33.3% of the variation in physical disability was explained by the model. In terms of functional limitations,multiple linear regression (MLR) model for cognitive functioning indicate that increasing age (p<0.01), unemployed (p<0.05) and those without formal education (p<0.01) predicts cognitive impairment with 25% of the variance in cognitive functioning was explained by the model. The predictors of mobility dependent were increasing age (p<0.001), without any formal education (p<0.01), never participate in any activity/social programs (p<0.01), rated their health poorly (p<0.001) and having high risk of falls (p<0.001) with 67% of the variance in mobility functioning was explained by the model. Factors that predict poor manual dexterity were increasing age (p<0.05), having poor social relations (p<0.001) and rated own health poorly (p<0.05) with 23% of the variance in manual dexterity was explained by the model. MLR model for muscle strength indicates that increasing age (p<0.05), being female (p<0.01), had formal education (p<0.05), having good/excellent perception on health (p<0.05), never consume alcohol (p<0.05), high risk of falls (p<0.001), and low skeletal muscle mass (SMM) (p<0.01) were the predictors of poor muscle strength with 64% of the variance in muscle strength was explained by the model. In conclusion, self-reported physical disability indicated a higher degree of poor functional status than functional limitation assessed by performance-based in this study, while association with socio-demographic and other health-related factors were consistent with other studies. Thus in a bigger perspective, any geriatricians intended to do research in the field of functional status should assess both self-report of physical disability and performance-based functional limitations, as it complements each other. Indeed, functional status assessment should be multidisciplinary involving several appropriate specialists, to identify and understand the factors considered to be the primary drivers of disability and limitations among elderly, in addition to devise and implement strategies for preventing or delaying the onset of functional decline in the elderly.